Assessing Projects’ Performance Of Iranian Construction Companies Through Application Of A Maturity Model - Mohammad , Khoshgoftar (2010)
Construction companies in today’s business environment of rapidly changing technology and fiercely competitive world seek excellence to succeed. Construction companies’ problems usually revolve project performance in terms of cost, time, quality and client satisfaction and may affect their competitiveness. It is vital for construction companies to adopt suitable methods, tools, or techniques that can help them to reduce these problems, assess and improve their project performance. This study aimed at establishing the relationship between the factors of a suitable maturity model and project performance.